Reasons for family refusal to donate córneas (Research, Society and Development, 2020)
This study aims to identify the reasons that lead to family refusal to donate corneas in an institution in the south of the country. A retrospective quantitative study of documentary character was carried out, with data collection through 102 medical records of patients whose family members were interviewed for corneal donation between the months of July to December 2013. As for family consent, a total of 70 negative and 30 positive family members for corneal donation, obtaining as the most frequent justification for family refusal, the prior conviction of the potential donor not to be an organ donor, the ignorance of the decision of the potential donor, followed by disagreement among family members. According to the research, the results suggest the importance of exploring and implementing strategies in order to attribute more social value to the donation, since it is not enough to just raise awareness among the population, it is also necessary that there are trained health professionals to efficiently coordinate all the process, and that can contribute to the planning and development of interventions that encourage the donation of tissues and organs.